Discussion on Control Model of Air Compressors Based on Multi-Agent - SHI Zhi-peng; LEI Ru-hai (Gong-kuang zidonghua, 2011)
For the problem of power consumption caused by delay of control mode of current air-compressed system used in mine, a control model of air compressors based on Multi-Agent was proposed by comparing with advantages and disadvantages of several control modes. Model framework of Multi-Agent was given, function and interaction mode of each Agent in the framework was described, feasibility of the model simulation was discussed, and a simulation way was put forward which uses object-oriented technology and ACL to simulate model.